"Scary" heterosexualities in a rural Australian mining town - Pini, Barbara; Mayes, Robyn; Boyer, K. (Elsevier Ltd, 2013)
This paper draws upon Hubbard's (1999, p. 57) term ‘scary heterosexualities,’ that is non-normative heterosexuality, in the context of the rural drawing on data from fieldwork in the remote Western Australian mining town of Kalgoorlie. Our focus is ‘the skimpie’ – a female barmaid who serves in her underwear and who, in both historical and contemporary times, is strongly associated with rural mining communities. Interviews with skimpies and local residents as well as participant observation reveal how potential fears and anxieties about skimpies are managed. We identify the discursive and spatial processes by which skimpie work is contained in Kalgoorlie so that the potential scariness ‘the skimpie’ represents to the rural is muted and buttressed in terms of a more conventional and less threatening rural heterosexuality.